Perspectives on semantics, pragmatics, and discourse : a Festschrift for Ferenc Kiefer - Kiefer, Ferenc; Kenesei, István; Harnish, Robert M. (Pragmatics & beyond, 2001)
Professor Ferenc Kiefer of the Linguistics Institute of the Hungarian Academy of Sciences was instrumental in bringing early transformational grammar to Europe. His extensive work contributes substantially to making a connection between the grammatical theory and other areas of linguistics. The 17 essays in this book celebrate his career by continuing to explore inter-area research in linguistics: pragmatics in grammar (de Groot, van Riemsdijk, Dressler & Barbaresi, Comrie), semantic compositionality and pragmatics (Wunderlich, Partee, Borschev, Szabo, Bach), logical structures and universals.